'I'm Working Towards Getting Back Together': Client Accounts of Motivation Related to Relationship Status in Men's Behaviour Change Programmes in New South Wales, Australia. (10th July 2014) - Gray, Rebecca; Broady, Timothy; Gaffney, Irene; Lewis, Pamela; Mokany, Tibor; O'Neill, Brian
Abstract : Research in Australia has examined factors associated with filicide in order to more accurately instigate points of intervention. Factors include parental separation/divorce, depression in the perpetrator and domestic violence. Therefore, services that facilitate men's behaviour change programmes provide one such point of intervention. Relationships Australia NSW offers 'Taking Responsibility': an 18‐week programme that addresses men's use of violence and abuse in their intimate relationships, through group work and individual support. Fundamental to this programme is the whole family's safety, which is managed through initial screening, ongoing contact and access to additional therapeutic services. Programme evaluation has revealed that men's change factors are influenced by varying levels of motivation, at intake and throughout. These accounts have indicated that the relationship status with their partner affects their motivation, which in turn has the potential to affect their investment in the programme. This relates to both increased and diminished motivation. Partners and former partners, however, expressed ambivalence towards their continuing relationships. Given the risk factors for filicide associated with domestic violence and separation, these interviews contribute to what is known about men's motivation to change violent and abusive behaviours, and in turn the clinical objectives for professionals working on these programmes. Copyright © 2014 John Wiley & Sons, Ltd. 'Fundamental to this programme is the whole family's safety' Key Practitioner Messages: The client's relationship status often changes throughout the course of a men's behaviour change programme. A separation can negatively affect motivation and behaviour change processes. Professionals working with men who use violence are advised to raise the topic of the client's relationship status, to prevent attrition, and work with them to broaden their motivations. 'A separation can negatively affect motivation and behaviour change processes'